The effect of vitamin D deficiency on the developing brain: a pilot study. (18th April 2012) - Kyriakopoulou, V; Vatansever, D; Dhodhia, SK; Allsop, JM; Fox, M; Hajnal, JV; Rutherford, MA
Abstract : Vitamin D deficiency during pregnancy is a common yet under recognised problem affecting 28% of Caucasians and 50% of Asians and African-Americans in the UK. Prenatal vitamin D deficiency in a rat pup model is associated with alterated brain morphology including ventriculomegaly and abnormal behaviour. To date, there is no study investigating the effect of maternal vitamin D deficiency in the human fetal brain. The aim of this study was to measure maternal vitamin D levels in stored booking bloods of normal control and isolated ventriculomegaly fetuses and to correlate vitamin D levels with ventricular and supratentorial brain volumes. Fetal brain MRI (1.5T) was performed in 11 normal control (mean 29 weeks; 23.14-36) and 16 isolated ventriculomegaly fetuses (mean 27.3 weeks; 22.14-37). Volumetric analysis of the lateral ventricles and supratentorial brain tissue was performed on 3D-reconstructed datasets. Vitamin D levels (D2+D3) were measured retrospectively in stored booking bloods using liquid chromatography-mass spectrometry. Vitamin D levels were significantly lower in women with darker skin or minimal sun exposure. Interestingly, D2 levels (obtained through diet) were recordable in only 2/27 women. There was no significant difference in vitamin D levels between normal control and ventriculomegaly fetuses. There was no significant correlation between vitamin D levels and ventricular or supratentorial brain tissue volume adjusted for gestational age. Our pilot data indicate that vitamin D levels can be successfully measured in stored booking bloods, however there was no correlation between vitamin D levels and brain development possibly due to the small sample size.